2007
DOI: 10.1021/es070198o
|View full text |Cite
|
Sign up to set email alerts
|

Metal Emissions from Brake Linings and Tires: Case Studies of Stockholm, Sweden 1995/1998 and 2005

Abstract: Road traffic has been highlighted as a major source of metal emissions in urban areas. Brake linings and tires are known emission sources of particulate matter to air; the aim of the current study was to follow the development of metal emissions from these sources over the period 1995/ 1998-2005, and to compare the emitted metal quantities to other metal emission sources. Stockholm, Sweden was chosen as a study site. The calculations were based on material metal concentrations, traffic volume, particle emissi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
162
1
6

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 372 publications
(185 citation statements)
references
References 11 publications
9
162
1
6
Order By: Relevance
“…[56][57][58] Extraction procedures similar to the ones described for soils have been applied to a limited extent to airborne particulate matter. [59,60] The operational character of such methods, and the limitations implied, remain the same as those discussed for other solid matrices.…”
Section: Atmospherementioning
confidence: 99%
“…[56][57][58] Extraction procedures similar to the ones described for soils have been applied to a limited extent to airborne particulate matter. [59,60] The operational character of such methods, and the limitations implied, remain the same as those discussed for other solid matrices.…”
Section: Atmospherementioning
confidence: 99%
“…The highly elevated Cu levels in the vehicle were similar to findings from Riediker et al (2003), which found elevated levels of a number of elements, particularly Cu and soil elements, in police patrol vehicles. Brake wear from vehicles is the likely source of Cu and Zn in the vehicle, as materials containing these elements have been incorporated into brake linings to replace asbestos (Hjortenkrans et al, 2007), whereas Zn also may be related to wear of tires (Legret and Pagotto, 1999). Riediker et al (2003) suggest that elevated soil elements in the vehicle, including Al, Ca, K and Ti, were likely from gasoline combustion and Fe from vehicle wear, but resuspension of road dust and erosion of roadway material are other potential sources as well.…”
Section: Me-ambient Ratios For Pm 25 Ec Oc and Elementsmentioning
confidence: 99%
“…Particles containing heavy metals such as Cd are released from vehicle tires and the burning of vehicle fuels (Chen et al, 2010), whereas the release of Zn may result from tire abrasion and lubricating oils (Adachi and Tainosho, 2004). Brake linings are one of the main sources of Cu (Adachi and Tainosho, 2004;Hjortenkrans et al, 2007); Pb is emitted from leaded fuels (Van Bohemen and Van De Laak, 2003) and Cr predominantly originates from oil residues and the abrasion of brake pads and tires (Zehetner et al, 2009). These particles are deposited into soils through dry and wet deposition, splashing and runoff (Werkenthin et al, 2014).…”
Section: Introductionmentioning
confidence: 99%